2003
DOI: 10.1515/bc.2003.164
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Transmembrane-Type Serine Protease from Rat Kidney, a New Sodium Channel Activator

Abstract: We have cloned the gene of a new transmembrane-type serine protease from rat kidney, which activates sodium channels. The amino acid sequence deduced from a full-length cDNA revealed that transmembrane serine protease-1 (TMSP-1) is a member of the clan SA/family S1 of serine proteases, comprising a 30 amino acid prepropeptide, a mature form sequence of 274 amino acids starting with the Ile-Val-Gly-Gly-Gln motif, and a common catalytic triad of serine proteases. The hydrophobic amino acid sequence in the carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Mammalian homologs of Xenopus CAP1, such as mouse mCAP1 or human and rat prostasin, were also shown to activate ENaC in the Xenopus oocyte expression system (1,11,38,39). More recently, additional transmembrane serine proteases activating ENaC have been identified in mammals, including channelactivating protease 2 (CAP2) and channel-activating protease 3 (CAP3) cloned from the mpkCCD d4 mouse kidney cell line (37), TMPRSS3 from human inner ear (15), or TMSP-1 from rat kidney (27). The precise mechanism for protease-mediated activation of ENaC has not been elucidated.…”
mentioning
confidence: 99%
“…Mammalian homologs of Xenopus CAP1, such as mouse mCAP1 or human and rat prostasin, were also shown to activate ENaC in the Xenopus oocyte expression system (1,11,38,39). More recently, additional transmembrane serine proteases activating ENaC have been identified in mammals, including channelactivating protease 2 (CAP2) and channel-activating protease 3 (CAP3) cloned from the mpkCCD d4 mouse kidney cell line (37), TMPRSS3 from human inner ear (15), or TMSP-1 from rat kidney (27). The precise mechanism for protease-mediated activation of ENaC has not been elucidated.…”
mentioning
confidence: 99%
“…It has been recently shown that ENaC channels expressed at the cell surface can be activated in vitro and in vivo by various trypsin-like serine proteases [ 10 - 14 , 17 , 27 ]. Membrane-bound Channel-Activating Proteases, which are co-expressed with ENaC in airway and alveolar epithelial cells [ 15 , 20 - 22 , 24 ] but also in other epithelial cells transporting Na + [ 12 , 14 ] have the ability to stimulate ENaC activity by increasing the channel opening probability, most likely through proteolytic cleavage of γ-ENaC subunit [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian homologs of Xenopus CAP1, such as mouse mCAP1 or human and rat prostasin, were also shown to activate ENaC in the Xenopus oocytes expression system [ 12 - 15 ]. More recently, additional transmembrane serine proteases activating ENaC have been identified in mammals, including channel-activating protease 2 (CAP2) and channel-activating protease 3 (CAP3) cloned from the mpkCCD d4 mouse kidney cell line [ 14 ], TMPRSS3 from human inner ear [ 16 ], or TMSP-1 from rat kidney [ 17 ]. The precise mechanism for protease-mediated activation of ENaC has not been fully elucidated, but it likely involves proteolytic cleavage of α- and γ-ENaC subunits [ 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation